2021
DOI: 10.1155/2021/4894881
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Promotes the Survival of the Grafted Human MGE Neural Progenitors in Rats with Cerebral Ischemia by Promoting Angiogenesis and Inhibiting Inflammation

Abstract: Stem cells have the potential as a regenerative therapy for cerebral ischemia by improving functional outcomes. However, cell transplantation has some limitations, including a low rate of the grafted cell survival. There is still a major challenge of promoting the harmonious symbiosis between grafted cells and the host. Acupuncture can effectively improve the functional outcome after cerebral ischemia. The present study evaluated the therapeutic effects and explored the mechanism of combined medial ganglionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…Electroacupuncture therapy was developed from traditional acupuncture, adding electrical stimulation to acupuncture therapy. Many studies have focused on mechanisms underlying the neuroprotective effect of electroacupuncture therapy, and some have shown that electroacupuncture improves neurological behavioral outcomes ( Deng et al, 2022 ), increases cerebral blood flow in the ischemic area ( Mei et al, 2020 ), inhibits neural inflammation and neural hypoxia ( Xu et al, 2018 ; Long et al, 2019 ), and promotes angiogenesis and neurogenesis ( Shi et al, 2017 ; Chen et al, 2020 ; Li et al, 2020 , 2021 ). Therefore, we selected GV20 and the left ST36 to treat the hemiplegia caused by CIRI in the rats.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture therapy was developed from traditional acupuncture, adding electrical stimulation to acupuncture therapy. Many studies have focused on mechanisms underlying the neuroprotective effect of electroacupuncture therapy, and some have shown that electroacupuncture improves neurological behavioral outcomes ( Deng et al, 2022 ), increases cerebral blood flow in the ischemic area ( Mei et al, 2020 ), inhibits neural inflammation and neural hypoxia ( Xu et al, 2018 ; Long et al, 2019 ), and promotes angiogenesis and neurogenesis ( Shi et al, 2017 ; Chen et al, 2020 ; Li et al, 2020 , 2021 ). Therefore, we selected GV20 and the left ST36 to treat the hemiplegia caused by CIRI in the rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to generate similar MGE cells through directed differentiation of human PSCs (hPSCs) (including hiPSCs and human ESCs). There is no lack of research on the generation of MGE-like neural progenitor cells from hPSCs, which then differentiate into GABAergic interneurons and mature in vitro ( Liu et al, 2013 ; Noakes et al, 2019 ; Li et al, 2021 ). Ground-breaking researches have shown that MGE cells derived from hPSCs can be used for the treatment of epilepsy ( Upadhya et al, 2019 ), neuropathic pain ( Fandel et al, 2016 ), and stroke ( Li et al, 2021 ), opening the possibility of developing suitable human therapies.…”
Section: Discussionmentioning
confidence: 99%
“…There is no lack of research on the generation of MGE-like neural progenitor cells from hPSCs, which then differentiate into GABAergic interneurons and mature in vitro ( Liu et al, 2013 ; Noakes et al, 2019 ; Li et al, 2021 ). Ground-breaking researches have shown that MGE cells derived from hPSCs can be used for the treatment of epilepsy ( Upadhya et al, 2019 ), neuropathic pain ( Fandel et al, 2016 ), and stroke ( Li et al, 2021 ), opening the possibility of developing suitable human therapies. If the efficiency of inducing differentiation can be improved and large-scale amplification of functional MGE progenitor cells can be achieved, this will greatly improve the accessibility of these cells ( Ma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis does not only increase collateral circulation to mitigate brain injury caused by ischemia, but exert a pivotal role in the recovery of neurological functions after ischemic stroke [ 14 , 15 ]. The regeneration of vascular structures provide necessary "support" for neurogenesis and synapse formation, and accelerates recovery of neural networks, which play an important role in improving the quality of life of stroke patients [ 16 , 17 ]. Angiogenesis is regulated by various vascular growth factors, which include classic angiogenesis factors such as vascular endothelial growth factor (VEGF), and non-classical angiogenesis factors such as erythropoietin (EPO).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our previous study showed that increased Src phosphorylation levels confer a protective effect in brain damage caused by ischemia [ 27 ]. Although there are reports that EA increases the expression of EPO, VEGF and p-Src in the brain tissue after ischemic stroke [ 16 , 28 , 29 ], data on how the three proteins interact to promote angiogenesis after EA remains unavailable. This study employed in vivo and in vitro experiments to explore the mechanisms of EA at the GV26 acupoint in CIRI rats by characterizing the relationship between EPO and VEGF in mediating angiogenesis.…”
Section: Introductionmentioning
confidence: 99%